2019
DOI: 10.1590/s1517-707620190002.0662
|View full text |Cite
|
Sign up to set email alerts
|

Study on impact of fiber hybridization in material properties of engineered cementitious composites

Abstract: ABSTRATO Compósito Cimentício Projetado (ECC) é um tipo de compósitos cimentícios reforçados com fibras de alto desempenho melhorados com bom comportamento de tração, compressão e flexão. O ECC é conhecido por seu comportamento de endurecimento de tensão sob tensão e tem sido cada vez mais aplicado na prática de engenharia. O processo de adicionar duas ou mais fibras em uma mistura é conhecido como hibridização. Os drives de compósitos híbridos se beneficiam de cada uma das fibras individuais adicionadas e exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…While using cactus mucilage as biopolymer in concrete carbonization rate increased and acted as a positive catalyst. [24][25][26] Sathya observed that lignocellulose in cactus, unsaturated, and saturated fatty acids made this admixture a retardant which eventually improved its strength [27]. The internal curing of concrete was achieved by using super adsorbent polymers [28] and plant extract [29,30], and the improvement in shrinkage of concrete was enhanced [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…While using cactus mucilage as biopolymer in concrete carbonization rate increased and acted as a positive catalyst. [24][25][26] Sathya observed that lignocellulose in cactus, unsaturated, and saturated fatty acids made this admixture a retardant which eventually improved its strength [27]. The internal curing of concrete was achieved by using super adsorbent polymers [28] and plant extract [29,30], and the improvement in shrinkage of concrete was enhanced [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of testing the single-lap joint and butt joint for both single and multiple bolt configurations, a specialized all-steel testing apparatus is constructed [68]. A horizontal load frame attached to a hydraulic jack that was specialized electrically with a digital display of load at the loading end is used.…”
Section: Laboratory Configurationmentioning
confidence: 99%
“…It consists of two cylindrical rings, (Krishnaraja, Anandakumar, Jegan, Mukesh, & Kumar, 2019) one of diameter 300 mm (inner cylinder) and the other 600 mm (outer cylinder) placed over the slab specimen of size 1000 mm and depth 100 mm as shown in Figure 4(b). Initially, water is poured into the cylinder (Susilorini et al, 2014) and then the rapidity of infiltration of the water is noted using the scale attached with respect to the time and depth of infiltration into the slab specimen using Eq.…”
Section: Infiltrationmentioning
confidence: 99%